Disiplin, Berani, dan Setia: Pembentuk Karakter Melalui Pendidikan Kepramukaan Racana Kusuma Dilaga–Woro Srikandhi UIN Salatiga - Mukti Ali; Mukammad Arief Mufti Habibi (Forum Pembina Pramuka PTKIN Se-Indonesia, 2023)
This research aims to build character through Racana Kusuma Dilaga-Woro Srikandhi UIN Salatiga Scouting Education in implementing one of the Dasa Darma Pramuka points, the eighth of its ten items. This study used the descriptive qualitative method. According to the approach used, the presence of researchers in this study is necessary. This research was conducted at Racana Kusuma Dilaga-Woro Srikandhi UIN Salatiga with management informants, members and alumnis of Racana. The data sources used are primary, including observation and interviews and secondary data in documentation. The study results show that character is a differentiator between individuals from one, namely the form of character that emanates from their behaviour. The content of the eighth Dasa Darma is the character of discipline, courage and loyalty. The character formation of the members of Racana Kusuma Dilaga-Woro Srikandhi is carried out through every activity carried out. The activities include Education and Training for Pandega Scout Candidates, coordination meetings, routine training, and SGT guidance (Siaga, Galang, Tegak). Every activity at Racana Kusuma Dilaga-Woro Srikandhi uses interesting, challenging, educational and fun methods that will make a person not feel bored and bored in learning.